Clinical and behavioral factors associated with undernutrition among highly active antiretroviral therapy users in Southwest Ethiopia - Shifera, Nigusie; Yosef, Tewodros; Mekonen, Mengistu (Frontiers in Nutrition, 2022)
Background: Globally, about 1.9 billion adults are overweight or obese, while 462 million are underweight. These are primarily found in countries with low and middle-incomes, like Ethiopia. Undernutrition is a frequent health problem among people living with HIV/AIDS; however, no large-scale research, including several health facilities has been conducted in Ethiopia. So this study aimed to assess the nutritional status and nutrition-related factors among highly active antiretroviral therapy (HAART) users in public hospitals in southwest Ethiopia. Methods: A cross-sectional facility study design was conducted in all public hospitals in southwest Ethiopia from January to March/2021. A systematic sampling technique was used to select the study participants. The collected data were entered into Epi-data 3.1, and then exported to SPSS version 24 for statistical analysis. Binary logistic regression analysis was done to identify the factors associated with the outcome variable. The level of significance was declared at a P-value of < 0.05 with their corresponding 95% confidence level. Results: A total of four hundred two highly active antiretroviral therapy users have participated with a 100% response rate. The proportion of undernutrition (BMI<18.5 kg/m2), and overweight or obese (BMI ≥25 kg/m2) patients were 29.3% [95% CI: (24.6-33.5)], and 10% [95% CI: (6.6-12.9)] respectively. Out of under-nutrition patients, severe malnutrition (BMI<16 kg/m2) accounted for 5.6%. Factors food insecurity [AOR: 3.21, 95% CI: (1.76-5.91)] History of diarrhea [AOR: 2.86, 95% CI: (1.96-6.78)], CD4 cell count ≤ [AOR: 4.72, 95% CI: (2.14-12.13)], and substance user [AOR: 4.12, 95% CI: (2.31-7.30)], were the independent factors of undernutrition. Conclusion: This study found that the prevalence of malnutrition was high compared to other settings. The government should also pay due attention to improving the treatment of HIV/AIDS by offering nutritional support services in hospitals. Moreover, policymakers and health care professionals consider the effects of these factors on nutrition while providing ART services.